IbM PELATIHAN DESAIN LABEL MAKANAN OLAHAN PADA SENTRA MAKANAN KECIL DI KELURAHAN TANJUNG - Herni Justiana Astuti; Fatmah Bagis; Maharani Retnaningrum (Media Ekonomi, 2017)
The aims of this IbM event are to give skill and knowledge about design and labelling food and beverage. The IbM was organized on food UMKM in Tanjung in which has 28 person. This event was performed by an economic and business faculty team of Muhammadiyah University of Purwokerto. The results of this IbM events is added knowledge and skill value about interested design and labelling of food and beverage and also added economic value of those product.